2002
DOI: 10.1016/s1062-1458(02)00701-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coronary artery remodeling and plaque vulnerability

Abstract: Background-In vivo studies with intravascular ultrasound have shown that complex plaque anatomy and plaque rupture are more frequent in the presence of marked outward remodeling. A large lipid core and a high macrophage count are recognized histological markers for plaque vulnerability. The link between plaque vulnerability in terms of these markers and remodeling in coronary arteries has not been explored. Methods and Results-In 88 male subjects who died suddenly with coronary artery disease, 108 plaques were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
205
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(220 citation statements)
references
References 8 publications
(8 reference statements)
11
205
1
3
Order By: Relevance
“…One characteristic of coronary artery remodeling is that in negative remodeling the plaque distribution is circumferential, while in positive remodeling the distribution of the plaque is mostly excentric. 5 In IVUS studies, the negative remodeling index was under 0.95, compared with positive remodeling where the remodeling index was below 1.05. Plaque calcium appears with shadowing and hyperechoic.…”
Section: Coronary Artery Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…One characteristic of coronary artery remodeling is that in negative remodeling the plaque distribution is circumferential, while in positive remodeling the distribution of the plaque is mostly excentric. 5 In IVUS studies, the negative remodeling index was under 0.95, compared with positive remodeling where the remodeling index was below 1.05. Plaque calcium appears with shadowing and hyperechoic.…”
Section: Coronary Artery Remodelingmentioning
confidence: 99%
“…In case of negative remodeling, lesions can be associated with a higher degree of stenosis. 5 Positive remodeling was shown to be related to acute coronary syndromes, and the external elastic membrane at the lesion site was larger compared with the reference segment; negative coronary remodeling is responsible for stenosis in patients with stable angina, and the external elastic membrane at the lesion site is much smaller compared to the reference segment. 6 By using IVUS, it was discovered that vessel shrinkage is correlated with a more circumferential distribution of the atheromatous plaque.…”
Section: Coronary Artery Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Furthermore, autopsy studies have shown that positive remodeling is associated with underlying lesions with the histological characteristics of plaque vulnerability, such as a large lipid core and high plaque macrophage content. 5 Under these conditions, OCT is not suitable for assessment of positive remodeling because of its limited penetration depth in a large vessel with plaque containing a large lipid core. Gray-scale IVUS remains the standard for assessing vessel dimensions and plaque volume and is the modality of choice for evaluating vessel remodeling; however, it has limited value for evaluating plaque characteristics such as lipid content.…”
Section: Article P 600mentioning
confidence: 99%
“…Glagov's positive remodelling) along the epicardial coronary arterial tree [2]. The positive remodelling may make the plaque vulnerable to rupture and potentially cause subsequent acute events [3].…”
Section: Introductionmentioning
confidence: 99%